Joint power allocation and beamforming for multiuser MIMO two-way relay networks - Khafagy, M.; El-Keyi, A.; ElBatt, T.; Nafie, M. (2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications, 2011)
In this paper, a multiuser cellular two-way relaying scenario is considered where multiple single-antenna mobile stations (MSs) and one multiple-antenna base station (BS) communicate, bidirectionally, via one half-duplex multiple-antenna relay station (RS). Furthermore, the case when the number of antennas at the RS is not sufficient to decode the individual messages is addressed. For this case, a two-phase two-way relaying scenario is considered. In the first phase, the multiple access, a minimum Mean Square Error (MSE) optimization problem is formulated which is found to be non-convex. Thus, an iterative scheme is proposed to compute the MS transmit powers, the BS beamforming vectors, and the corresponding RS linear receivers to minimize the maximum MSE for multiple pairs subject to power constraints on the transmitting terminals. In the second phase, the broadcast phase, the beamforming vectors at the RS are designed to minimize the maximum MSE at the MSs subject to relay power constraints, and the receivers at the BS are designed accordingly. In a two-pair scenario, simulation results are provided showing the superior performance of the proposed methods compared to earlier approaches in terms of the bit-error rate. Also, it is shown that as the system scales up in terms of signal space dimensions and number of accommodated pairs, the performance gap between the proposed scheme and the earlier approaches increases.